A comparison of patients with epileptic seizures (ES) versus those with psychogenic non-epileptic seizures (PNES) on measures of alexithymia, mood, and anxiety - Trobliger, Robert; Myers, Lorna; Simpson, Talia; Krámská, Lenka (Seizure, 2024)
OBJECTIVE: To compare persons with epilepsy (PWE) to those with psychogenic non-epileptic seizures (PNES) on measures of depression, anxiety, and alexithymia subscales (i.e., difficulty identifying emotions, difficulty describing emotions, and external-oriented thinking). MATERIAL AND METHODS: In this retrospective study, 235 epilepsy patients and 90 patients with PNES were evaluated between 2012 and 2020 at the Northeast Regional Epilepsy Group. These patients had completed the Toronto Alexithymia Scale (TAS-20), The Center for Epidemiologic Studies - Depression Scale (CES-D) and The State-Trait Anxiety Inventory (STAI). Background information was collected regarding work/student/disability status at the time of the evaluation history of psychiatric diagnosis; psychological trauma; and involvement in psychotherapy either at the time of the evaluation or prior. RESULTS: Significant differences between PWEs and those with PNES were found not only in historical data (e.g., Psychiatric History, History of Trauma, and History of Therapy) (p < .001) but also on measures of Depression (p = .002) and Anxiety (p < .001). ANOVA analysis also revealed significant differences in the distribution of the TAS-Total score, TAS-Describing emotions, and TAS-Identifying emotions. Using logistic regression (stepwise model) the optimal set of predictors for a differential diagnosis of epilepsy and PNES was combination of TAS-Identifying emotions score, history of psychological trauma, and history of therapy. The accuracy of the prediction was determined to be 80.2 %. CONCLUSIONS: Although higher alexithymia rates are present in PNES and PWEs, clinicians may find a combination of TAS-Identifying Emotion score, history of trauma, and history of psychotherapy useful in supporting a differential diagnosis. Also, a subgroup may exist among those with PNES with high levels of alexithymia, depression, and anxiety that may require a different treatment approach focused on addressing difficulties in identifying and describing their emotions and their other symptomatology.
Keywords: Functional dissociative seizures; záchvaty; psychiatrické posuzovací škály; Psychiatric Status Rating Scales; deprese; Epilepsy; afektivní symptomy; epilepsie; Retrospective Studies; Functional neurological disorders; Depression; Middle Aged; mužské pohlaví; Affective Symptoms; Adult; mladý dospělý; Seizures; afekt; Young Adult; ženské pohlaví; Affect; retrospektivní studie; Humans; úzkost; Epileptic seizures; Anxiety; lidé středního věku; Alexithymia; dospělí; Female; lidé; Male